PENGARUH JUMLAH PENDUDUK, PENDAPATAN PERKAPITA, INFLASI, DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENERIMAAN PAJAK DAERAH (Studi kasus Kabupaten/Kota Propinsi Jawa Tengah Tahun 2011-2013) - Asep Putra Digdaya, 11.05.52.0081; Darso, Maryono (Students Journal of Accounting and Banking, 2015)
Changes in the law that took effect makes local tax revenues have greater income and the factors that influence it became more. This study aimed to analyze the influence of population, per capita income, inflation, and the regional gross domestic product (GDP) of the local tax revenue in 2011-2013. The purpose of this study was to determine the influence of population, per capita income, inflation, and the regional gross domestic product (GDP) of the local tax revenueThe sample used in this study was 35 District / City in 2011-2013. The sampling method used is cluster sampling method. This technique is used to determine the sample to be studied object or source data is very broad. 105 sample is obtained from the Central Statistics Agency (BPS), Central Java Province. The method used in this study is multiple regression analysis to determine the effect of the independent variable on the dependent variable. Techniques of data analysis and hypothesis testing using SPSS version 19 softwere.The results of this study showed that the number of negative and significant population of the local tax revenue, per capita income and a significant positive effect on local tax revenues, inflation is positive and significant impact on the local tax revenue, and gross regional domestic product (GRDP) positive and significant impact on the acceptance local taxes.Keywords: Local Taxes, Total Population, Per Capita Income, Inflation, and the Gross Domestic Product (GDP).